"Implicit" contestations of EU foreign policy norm-domestication in Bosnia and Herzegovina and North Macedonia. Issue 4 (19th October 2020) - Hasić, Jasmin; Džananović, Nedžma; Ramić Mesihović, Lejla
ABSTRACT: This article focuses on scrutinizing EU's norm-setting practices toward the Western Balkan (WB6) countries through identifying particular points of norm-acceleration and norm-resistance related to EU' foreign policy and enlargement objectives in developing "good neighborly relations" (GNR) regionally. Although the EU has repeatedly attempted to diffuse its foreign policy and enlargement-related norms to promote regional stability, development and cooperative relations across the WB6 countries, we posit that two policies are not always complimentary and that domestication of these norms in some countries still remains nationally contextualized and guided by specific dynamics. This article explores the factors that promote or mitigate the domestication of EU-induced norms in two selected countries, Bosnia and Herzegovina and North Macedonia. By examining these two cases separately, we argue the current norm domestication patterns in both countries stave off these "coded" EU-induced normative perspectives on GNR, mainly because of their strong mixture with the "non-codified" enlargement criteria.